Effect of Urinary Incontinence and Its Subtypes on Quality of Life of Women in Eastern Turkey - Firdolas, Fatih; Onur, Rahmi; Deveci, Suleyman Erhan; Rahman, Suheyla; Sevindik, Feyza; Acik, Yasemin (Elsevier Science Inc, 2012)
OBJECTIVE To determine the bothersomeness and effect on quality of life (QOL) of different types of urinary incontinence (UI) in married women living in eastern Turkey. MATERIALS AND METHODS A total of 1049 married women was evaluated in the present population-based, cross-sectional study. QOL was assessed using a validated form of the Turkish version of the Incontinence Impact Questionnaire Short Form. The effects of UI subtype on the overall QOL score and on the individual domain scores were determined. The relationship between several demographic characteristics such as age, weight, education level, number of pregnancies, number of live deliveries, and presence of pelvic organ prolapse and the QOL changes was examined. RESULTS The mean age of the women was 44.62 +/- 11.01 years (range 17-80). Of the women with UI, 76.2% stated that the UI had a negative effect on their QOL. Women with mixed UI and severe UI had the worst QOL scores. The QOL changes for the different domains revealed that entertainment activities were affected least, and emotional health and feelings of frustration were the 2 domains that showed the most significant deterioration. Furthermore, older and unemployed women, housewives, women living in urban areas, and women with multiple births, difficult labor, and increased weight experienced significant negative effects on their QOL. CONCLUSION Our results have shown that, regardless of different factors, UI has significant negative effects on QOL. The presented data emphasize the importance of the high prevalence of UI in our region and its negative effects on QOL. Thus, additional policies are needed for the prevention of the negative effects of UI. UROLOGY 80: 1221-1226, 2012. (C) 2012 Elsevier Inc.
Keywords: Risk-Factors; Impact Questionnaire; Overactive Bladder; Short Forms; Prevalence; Seeking; Community; Distress; Help